Treating Influenza Infection, From Now and Into the Future - Davidson, Sophia (Frontiers in Immunology, 2018)
Influenza viruses (IVs) are a continual threat to global health. The high mutation rate of the IV genome makes this virus incredibly successful, genetic drift allows for annual epidemics which result in thousands of deaths and millions of hospitalizations. Moreover, the emergence of new strains through genetic shift (e.g. swine-origin influenza A) can cause devastating global outbreaks of infection. Neuraminidase inhibitors (NAIs) are currently used to treat IV infection and act directly on viral proteins to halt IV spread. However, effectivity is limited late in infection and drug resistance can develop. New therapies which target highly conserved features of IV such as antibodies to the stem region of hemagglutinin or the IV RNA polymerase inhibitor: Favipiravir are currently in clinical trials. Compared to NAIs these treatments have a higher tolerance for resistance and a longer therapeutic window and thus, may prove more effective. However, clinical and experimental evidence demonstrates that the host inflammatory response and damage to the lung epithelium are key events which dictate the outcome of IV infection. Therapeutic regimens for IV infection should therefore also regulate the host inflammatory response and protect epithelial cells from unnecessary cell death. Anti-inflammatory drugs such as etanercept, statins or cyclooxygenase enzyme 2 inhibitors may temper IV induced inflammation, demonstrating the possibility of repurposing these drugs as single or adjunct therapies for IV infection. IV binds to sialic acid receptors on the host cell surface to initiate infection and productive IV replication is primarily restricted to airway epithelial cells. Accordingly, targeting therapies to the epithelium will directly inhibit IV spread while minimising off target consequences, such as over activation of immune cells. The neuraminidase mimic Fludase cleaves sialic acid receptors from the epithelium to inhibit IV entry to cells. While type III interferons activate an antiviral gene program in epithelial cells with minimal perturbation to the IV specific immune response. This review discusses the above-mentioned candidate anti-IV therapeutics and others at the preclinical and clinical trial stage.